Baby-Boom, Baby-Bust and the Great Depression - Andriana Bellou; Emanuela Cardia (Institute for the Study of Labor (IZA), 2014)
The baby-boom and subsequent baby-bust have shaped much of the history of the second half of the 20th century; yet it is still largely unclear what caused them. This paper presents a new unified explanation of the fertility Boom-Bust that links the latter to the Great Depression and the subsequent economic recovery. We show that the 1929 Crash attracted young married women 20 to 34 years old in 1930 (whom we name D-cohort) in the labor market possibly via an added worker effect. Using several years of Census micro data, we further document that the same cohort kept entering into the market in the 1940s and 1950s as economic conditions improved, decreasing wages and reducing work incentives for younger women. Its retirement in the late 1950s and in the 1960s instead freed positions and created employment opportunities. Finally, we show that the entry of the D-cohort is associated with increased births in the 1950s, while its retirement turned the fertility Boom into a Bust in the 1960s. The work behavior of this cohort explains a large share of the changes in both yearly births and completed fertility of all cohorts involved.
Keywords: J11; J12; J13; J21; J24; J26; J31; 330; retirement; added worker effect; Great Depression; baby bust; baby boom; fertility